Lyric Contingencies : Emily Dickinson and Wallace Stevens - Dickie, Margaret (University of Pennsylvania Press, 2016)
In Lyric Contingencies Margaret Dickie brings Wallace Stevens and Emily Dickinson together to explore the ways in which the lyric genre is eccentric to, even disruptive of, the Emersonian tradition that has shaped American literary history. Dickie contends that although Stevens and Dickinson represent different moments of cultural crises, different genders, and different and private lives, they faced similar problems of expression and similar formal and cultural restraints in their devotion to the lyric genre. Dickie considers those elements of the lyric that set it apart from both prose and narrative poetry: its speaker, its insistence on artifice, and its relation to an audience. By concentrating on these, she examines the radically experimental ways in which Dickinson and Stevens used the genre to question cultural certainties of gender, language, and the nature of the individual.